Community health worker caseloads, home visits, and child survival: Experimental evidence of heterogenous effects from Mali - Allen IV, James (International Food Policy Research Institute, 2025)
I examine whether the effectiveness of community health worker (CHW) home visits in reducing under-five mortality varies with the population-to-CHW ratio in rural, fragile, and conflict-affected Mali. Muso, a global health NGO focused on reducing child and maternal mortality, recently signed a data use agreement with IFPRI to enable study of new research questions using data from its recent randomized controlled trial (RCT) of proactive home visits in Mali’s Bankass region. The original trial found that proactive home visits by professional CHWs did not lead to detectable reductions in child mortality relative to fixed-site care, although health infrastructure improvements in both treatment arms likely led to experienced large declines in under-five mortality across all study communities amid ongoing conflict.